EFFECTS OF A SELECTED HERBAL BEVERAGE ON THE FULL HAEM OGRAM, INFLAMMATION AND SERUM ZINC STATUS OF HIV AND AIDS SUBJECTS IN NAIROBI, KENYA, 2010 - Nagel, Friederike Deborah; Mbakaya, Prof. Charles F.L.; Kombe, Dr. Yeri I.; Nyambati, Dr. Venny C. S. (Global Journal of Health Sciences, 2016)
Purpose: The purpose of the study was to establish the effects of a selected herbal beverage on the full Haemogram, inflammation and serum zinc status of HIV and AIDS Subjects in Nairobi, Kenya. Methodology: This was a randomized prospective controlled intervention study. The sample size was 100 patients who were recruited from the Association of People living With AIDS in Kenya (TAPWAK) that is based at Nairobi West. The study subjects were recruited upon consent and randomized into the two groups, one group received the herbal beverage and the other a placebo. The intervention was double blinded and unmasking was done during data analysis. Blood samples were taken from the subjects at baseline and periodically, to investigate effects on or changes in the above biomarkers. Means and medians of the biomarkers were compared between and within groups at baseline and at end line. Results: Following the study findings it was possible to conclude that regarding the socio-economic status of the study subjects in both arms were comparable by marital status. Majority of subjects had children who depended on them. By education status, the subjects were comparable between the groups. Most of the subjects had attained some level of education, those on the intervention arm having a higher proportion of more educated persons. While about half the subjects had social support systems, financial support was lacking for close to 80% of the subjects in both arms. Women were a majority in both study arms, one reason could be that they are more willing to get help for issues affecting their health. The Erythrocyte Sedimentation Rate (ESR) count was not different at baseline in both groups but almost attained significant difference at the 9th month of intervention, the intervention group having a much lower value (p = 0.074), suggesting that the mode of action of the herbal beverage was via reduction of inflammation. The same was the trend in the Mean Corpuscular Hemoglobin Concentration MCHC, the intervention arm having a lower value than the placebo group (p = 0.088). However, the other hematological parameters were neither different at baseline nor at the 9th month of intervention. The serum zinc values in the intervention and placebo arms were similar at baseline, 3rd, 6th and 9th months and lower than normal values at all time points, suggesting that the intervention had no benefits in repletion of serum zinc levels and / or no effect in improved absorption of serum zinc of the subjects, yet this trace element is critical in human immunity. The median platelet (PLT) count was much lower in the intervention arm than the placebo at the 9th month of intervention (p = 0.045) while they were not different at baseline (p = 0.332), again suggesting that the mode of action of the herbal beverage might be via PLT reduction. Overall, the benefits of the herbal beverage were only marginally better in the intervention arm than the placebo for most of the selected biomarkers assessed in this study. Unique contribution to theory, practice and policy: The study recommended that despite interesting finding regarding the impact of the ESR count of patients of the intervention group which could suggest that consumption of the herbal beverage in combination with an effective medical based treatment of HIV/ Aids could be promising for improvement of inflammation regulation in the patients. Further studies on that would be of benefit.